Integrasi Aplikasi Pengelolaan Keuangan untuk Mendukung Sistem Penyusunan Laporan Keuangan Pemerintah Daerah Terpadu Provinsi XYZ - Mustakim, M. (UM Purwokerto Press, 2023)
Province XYZ Government has several application systems to support financial management and reporting system like budgeting and treasury system, asset management system and accounting system. All systems are working separately which may cause data to exist only in one of those systems when another system is needed for those data. They need integration among those systems to have more beneficiaries from the systems. This research used Enterprise Application Integration (EAI) to confront the problem. We used data level integration to integrate the asset management system and accounting system and application interface level integration using APIs to integrate the budgeting and treasury system and accounting system. Our experiment results that data-level integration is simpler to develop than application interface-level integration. Application interface level integration needed more prerequisite requirements and is more difficult to develop but more flexible and secure to connect and integrate into another system. Our performance test shows that integration using APIs needs more resources and probably gives a problem when the text data that is interchanged is too big. When all systems are owned by one institution that does not need restricted security constraints, data level integration gave more benefit for institution system integration.